Delay in glucose peak time during the oral glucose tolerance test as an indicator of insulin resistance and insulin secretion in type 2 diabetes patients. Issue 6 (20th April 2018) - Wang, Xinlei; Zhao, Xiaoqin; Zhou, Ranran; Gu, Yunjuan; Zhu, Xiaohui; Tang, Zhuqi; Yuan, Xinlu; Chen, Wei; Zhang, Rongping; Qian, Chen; Cui, Shiwei
Abstract: Aims/Introduction: Previous studies have shown that glucose peak time during the oral glucose tolerance test varies in type 2 diabetes patients; however, characteristics of this heterogeneity remain unclear. This research aimed to investigate the characteristics of delayed glucose peak time in type 2 diabetes. Materials and Methods: A total of 178 participants who underwent the oral glucose tolerance test were divided into five groups according to glucose peak time. Results: A total of 25 participants with normal glucose tolerance had a glucose peak at 30 min. Among participants with type 2 diabetes, 28 had a glucose peak at 60 min, 48 at 90 min, 45 at 120 min and 32 at 150 min. With the glucose peak time delayed, glycated hemoglobin, area under the glucose curve and homeostatic model assessment of insulin resistance increased gradually ( P = 0.038, P < 0.0001, P < 0.0001, respectively), and oral glucose insulin sensitivity, homeostatic model assessment of β‐cell function, insulinogenic index, modified β‐cell function index and disposition indices decreased ( P < 0.0001 for all). On multinominal logistic regression, insulinogenic index (odds ratio 0.73, 95% confidence interval 0.57–0.93, P = 0.01), modified β‐cell function index (odds ratio 0.67, 95% confidence interval 0.47–0.94, P = 0.023) and oral glucose insulin sensitivity (odds ratio 0.91, 95% confidence interval 0.87–0.96, P < 0.0001) were independently correlated with delayed glucose peak time. Conclusions: Delay in glucose peak time indicated an increase in blood glucose and a decrease in insulin sensitivity and secretion. Furthermore, insulinogenic index, modified β‐cell function index and oral glucose insulin sensitivity contributed to delayed glucose peak time. Abstract : The purpose of this research was to investigate the characteristics of delayed glucose peak time of type 2 diabetes. Along with the delay of glucose peak time, blood glucose increased while insulin sensitivity and secretion decreased. Insulinogenic index, modified beta‐cell function index, oral glucose insulin sensitivity contributed to delayed glucose peak time.